The Relationship Between Hardiness Personality and Burnout in North Sumatra Regional Police Brimob Personnel - Hasibuan, Yuli Sumiati; Ambarita, Togi Fitri A (Jurnal Ilmu Sosial dan Humaniora, 2026)
Hardiness Personality, Burnout, Brimob Personnel This study aims to examine the Relationship Between Hardiness Personality and Burnout in Brimob Personnel of North Sumatra Regional Police. In this section, a number of conclusions obtained from the results of the research that has been carried out will be presented, accompanied by several practical and methodological suggestions for further research. Based on the results of the data analysis that has been carried out, the following conclusions can be drawn Based on the research that has been carried out, it shows that there is a negative relationship of -0.402 between hardiness personality and burnout in Brimob Personnel of North Sumatra Regional Police with a significance value of 0.000, so that the established hypothesis can be accepted. This means that the higher the hardiness personality, the lower the burnout experienced by Brimob Personnel of North Sumatra Regional Police. From the results of categorization based on variables, it can be seen that in the hardiness personality variable, Brimob Personnel of North Sumatra Regional Police are in the high category, namely 94 out of a total of 100 respondents. This shows that most Personnel have relatively high hardiness personality abilities. Furthermore, based on the categorization results of the burnout variable, the majority of personnel are in the low category, namely 52 people (53%), the medium category is 4 people (4%), and the high category is 44 people (44%). Therefore, burnout